Conformer and pharmacophore based identification of peptidomimetic inhibitors of chikungunya virus nsP2 protease. Issue 16 (10th December 2017) - Dhindwal, Sonali; Kesari, Pooja; Singh, Harvijay; Kumar, Pravindra; Tomar, Shailly
Abstract : Chikungunya virus nsP2 replication protein is a cysteine protease, which cleaves the nonstructural nsP1234 polyprotein into functional replication components. The cleavage and processing of nsP1234 by nsP2 protease is essential for the replication and proliferation of the virus. Thus, ChikV nsP2 protease is a promising target for antiviral drug discovery. In this study, the crystal structure of the C-terminal domain of ChikV nsP2 protease (PDB ID: 4ZTB) was used for structure based identification and rational designing of peptidomimetic inhibitors against nsP2 protease. The interactions of the junction residues of nsP3/4 polyprotein in the active site of nsP2 protease have been mimicked to identify and design potential inhibitory molecules. Molecular docking of the nsP3/4 junction peptide in the active site of ChikV nsP2 protease provided the structural insight of the probable binding mode of nsP3/4 peptide and pigeonholed the molecular interactions critical for the substrate binding. Further, the shape and pharmacophoric properties of the viral nsP3/4 substrate peptide were taken into consideration and the mimetic molecules were identified and designed. The designed mimetic compounds were then analyzed by docking and their binding affinity was assessed by molecular dynamics simulations.